Uso do teste timed up and go na avaliação da mobilidade funcional de pessoas com doença de Parkinson com e sem congelamento da marcha - Morais, Cristiane Ramos de (2022)
Background: People with Parkinson's Disease (PD) often have disabling gait disorders. Freezing of gait (FOG) is described as the sudden inability to start or continue walking, and is a disabling symptom. Objective: The main objective of this investigation is to evaluate the functional mobility of the individual with PD, with and without FOG, through the Timed Up and Go Test and correlated it with the clinical evaluation of the disease. Methods: A cross-sectional observational study was carried out with patients with PD and a control group using the Timed Up and Go (TUG) test, and a systematic clinical evaluation in people with PD using the Mini Mental, the MDS-UPDRS scale (parts II and III) and the New-FOG Questionnaire (NFOG-Q). Results: The difference between the mean TUG of the PD Group in OFF and the mean TUG of the Control Group was statistically significant. There was a significant difference in TUG between the OFF and ON states for the GFOG+ group, however, no difference was found for the GFOG-. For the GFOG+ group, there was a correlation between the TUG mean, in the OFF and ON states, and the sum of the MDS-UPDRS parts II and III scores. This correlation was not found for the GFOG-. Conclusion: Functional mobility is influenced by Parkinson's disease and medication status (ON and OFF). Thus, the functional assessment of gait through the TUG Test can help in the choice of rehabilitation strategies to optimize the pharmacological treatment in PD.